Evolution of plasma wakes in density up- and down-ramps. (3rd January 2018) - Zhang, C J; Joshi, C; Xu, X L; Mori, W B; Li, F; Wan, Y; Hua, J F; Pai, C H; Wang, J; Lu, W
Abstract: The time evolution of plasma wakes in density up- and down-ramps is examined through theory and particle-in-cell simulations. Motivated by observation of the reversal of a linear plasma wake in a plasma density upramp in a recent experiment (Zhang et al 2017 Phys. Rev. Lett. 119 064801) we have examined the behaviour of wakes in plasma ramps that always accompany any plasma source used for plasma-based acceleration. In the up-ramp case it is found that, after the passage of the drive pulse, the wavnumber/wavelength of the wake starts to decrease/increase with time until it eventually tends to zero/infinity, then the wake reverses its propagation direction and the wavenunber/wavelength of the wake begins to increase/shrink. The evolutions of the wavenumber and the phase velocity of the wake as functions of time are shown to be significantly different in the up-ramp and the down-ramp cases. In the latter case the wavenumber of the wake at a particular position in the ramp increases until the wake is eventually damped. It is also shown that the waveform of the wake at a particular time after being excited can be precisely controlled by tuning the initial plasma density profile, which may enable a new type of plasma-based ultrafast optics.